Cathelicidin Attenuates Hyperoxia-Induced Lung Injury by Inhibiting Ferroptosis in Newborn Rats - Hsiu-Chu Chou; Chung-Ming Chen (MDPI AG, 2022)
High oxygen concentrations are often required to treat newborn infants with respiratory distress but have adverse effects, such as increased oxidative stress and ferroptosis and impaired alveolarization. Cathelicidins are a family of antimicrobial peptides that exhibit antioxidant activity, and they can reduce hyperoxia-induced oxidative stress. This study evaluated the effects of cathelicidin treatment on lung ferroptosis and alveolarization in hyperoxia-exposed newborn rats. Sprague Dawley rat pups were either reared in room air (RA) or hyperoxia (85% O2) and then randomly given cathelicidin (8 mg/kg) in 0.05 mL of normal saline (NS), or NS was administered intraperitoneally on postnatal days from 1-6. The four groups obtained were as follows: RA + NS, RA + cathelicidin, O2 + NS, and O2 + cathelicidin. On postnatal day 7, lungs were harvested for histological, biochemical, and Western blot analyses. The rats nurtured in hyperoxia and treated with NS exhibited significantly lower body weight and cathelicidin expression, higher Fe2+, malondialdehyde, iron deposition, mitochondrial damage (TOMM20), and interleukin-1β (IL-1β), and significantly lower glutathione, glutathione peroxidase 4, and radial alveolar count (RAC) compared to the rats kept in RA and treated with NS or cathelicidin. Cathelicidin treatment mitigated hyperoxia-induced lung injury, as demonstrated by higher RAC and lower TOMM20 and IL-1β levels. The attenuation of lung injury was accompanied by decreased ferroptosis. These findings indicated that cathelicidin mitigated hyperoxia-induced lung injury in the rats, most likely by inhibiting ferroptosis.